A finite sequence of Hahn-type discrete orthogonal polynomials. Issue 7 (2nd July 2020) - Masjed-Jamei, Mohammad; Koepf, Wolfram; Tcheutia, Daniel Duviol
ABSTRACT: By considering a specific Sturm–Liouville problem, we introduce a finite sequence of Hahn-type discrete polynomials and prove that they are finitely orthogonal on the real line. We then compute their norm square value by using Dougall's bilateral sum and obtain all moments corresponding to the introduced polynomials.